2019
DOI: 10.1098/rsif.2019.0536
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying segregation in an integrated urban physical-social space

Abstract: Our knowledge of how cities bring together different social classes is still limited. Much effort has been devoted to investigating residential segregation, mostly over well-defined social groups (e.g. race). Little is known of how mobility and human communications affect urban social integration. The dynamics of spatial and social-network segregation and individual variations along these two dimensions are largely untapped. In this article, we put forward a computational framework based on coupling la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 55 publications
1
38
0
5
Order By: Relevance
“…Social networks are on the one hand the medium for information that influences the choice of place of residence, but also on the other hand a source of social support. The choice to live in close proximity to co-ethnic groups can mitigate the cultural shock on arrival and help people to adapt to the host society (van Kempen & Özüekren, 1998;Xu, Belyi, Santi, & Ratti, 2019). Alternatively, is the result of different sets of possible residential options for ethnic groups and their descendants (Krysan & Crowder, 2017).…”
Section: Social Network and Segregation In The Activity Spacementioning
confidence: 99%
“…Social networks are on the one hand the medium for information that influences the choice of place of residence, but also on the other hand a source of social support. The choice to live in close proximity to co-ethnic groups can mitigate the cultural shock on arrival and help people to adapt to the host society (van Kempen & Özüekren, 1998;Xu, Belyi, Santi, & Ratti, 2019). Alternatively, is the result of different sets of possible residential options for ethnic groups and their descendants (Krysan & Crowder, 2017).…”
Section: Social Network and Segregation In The Activity Spacementioning
confidence: 99%
“…al. [61] combined information on human mobility from mobile phone data with social-network connections and people's socio-economic status in order to depict dynamics of human segregation, which also suggest here that seemingly homogeneous urban populations groups are not equally at risk to suffer harm from climate-related hazards.…”
Section: Urban Population Susceptibilitymentioning
confidence: 99%
“…Some even credit the circulation of people throughout a city with the superlinear production of income and innovation [ 2 ]. However, a growing body of literature suggests that this circulation of people may be quite irregular: researchers have used high-granularity geospatial mobility datasets from Twitter or mobile phone data to identify individuals’ trajectories around cities and found that people are significantly more likely to colocate with others “like” them across various socioeconomic dimensions [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, studying location-connectivity as opposed to person-connectivity bypasses some of the obstacles that come with more traditional approaches. One such obstacle is that existing literature on segregation in activity spaces either relies on travel diaries and surveys [ 11 , 12 ], or on dense geospatial datasets that come from social media or mobile phones like the Twitter dataset that we use [ 3 – 5 , 7 , 8 ]. Survey-based methods produce rich data but are limited by sample size constraints and the reliability of respondents.…”
Section: Introductionmentioning
confidence: 99%